The principle of fair play in the aspect of responsibility in the opinion of junior high schools students-supporting sport clubs in Lodz - Kowalska, Jolanta Elżbieta (Journal of Education, Health and Sport, 2018)
The idea of fair play can play an important role in the education process, especially among students of adolescence (middle school age). In Lodz, this is particularly important because there is a problem of stadium hooliganism, which is particularly acute due to the competition between fans of two sports clubs..Therefore, it was important to undertake such educational activities (implementation of an educational project) so that the youth could understand exactly what the principle of fair play is only in sport, but in life, in all its aspects. After the implementation of the educational project „I am fair” dedicated to lower class of secondary schools’ pupils in Łódź (14-15 y.o.), it was decided to evaluate if and to what extent, students who took part in the project, had changed their awareness and declared behaviour of fair play in the aspect of responsibility in sport and life- among the declaring supporters and non-supporters of the selected football club as well. Material and methods: The study was conducted by diagnostic survey using a situational test "Fair play in sport and life". The results were analysed taking into account the change in the responses of students completed the questionnaire twice: before (pre- test) and after (post- test) the implementation of the project, taking into account the all respondents (1,377 people) and variable - the declaration of supporting or not the football, gender. The study was conducted in two waves- in September 2011 (pre- test) and June 2012 (post- test). Results: Results of post- test survey proved the improvement of declared behaviour among all tested groups and club supporters - boys, girls. On the one hand, sport contributes to the escalation of undesirable behaviours, on the other hand it becomes an educational tool. Education supported by fair play values brings expected effects and desirable changes, both in sport and in life.